Linking the evidence between urinary retention and antipsychotic or antidepressant drugs: A systematic review. Issue 8 (19th August 2015) - Faure Walker, Nicholas; Brinchmann, Katherine; Batura, Deepak
Abstract : Aims: Urinary retention (UR) occurs in patients on antipsychotic and antidepressant medication despite no apparent underlying urological cause. This review was undertaken to ascertain which of these medications are associated with UR and how often. Methods: A systematic literature search for evidence on antipsychotic and antidepressant medications and UR was completed in June 2015 using Scopus, Pubmed, Web of Science, and the Cochrane library. Search terms included urinary retention, antidepressants and antipsychotics as well as individual drug names. Filters used were: humans and English language. PRISMA guidelines were employed. Results: Out of 614 articles initially identified, one meta‐analysis, five RCT's, five cohort studies and 27 case reports were finally included. There was a wide range of definitions of UR. Studies which appropriately defined UR revealed it occurred in 1/21 patients on ziprasidone (an atypical antipsychotic), 17.6% of those on imipramine but only 0.1% of those on all tricyclic antidepressants analysed together. It was not reported in any of the 1, 139 patients given duloxetine (a combined serotonin and noradrenaline reuptake inhibitor). It was reported in 0.025% of patients on selective serotonin reuptake inhibitors. UR was also reported in patients on typical antispychotics, selective noradrenaline reuptake inhibitors but the studies did not define UR. The majority of case reports reported an improvement in UR on discontinuation or dose reduction. Conclusion: Antipsychotics and antidepressants interact with the urinary system in many ways. Clinicians treating acute UR need to keep in mind the role of antipsychotic and antidepressants as a precipitating cause. Neurourol. Urodynam. 35:866–874, 2016 . © 2015 Wiley Periodicals, Inc.